Optimization of Payroll System in the Education Sector of Timor-Leste: Ensuring Accuracy and Equity for Civil Servants and Teachers, A Case Study at the Ministry of Education in Dili - Gomes, Jeremias; Drahen, Pantius Soeling; Gomes, Martina Rupidara (Technium Sustainability, 2024)
This study has the objective of enhancing the precision and equity of the payroll system within the education sector of Timor-Leste. By concentrating on crucial components such as compensation, incentives, auditing and control mechanisms, as well as level/scale adjustments, welfare, and professionalism, this investigation tackles significant concerns. Timor-Leste, having gained independence in 2002, encounters notable hurdles in administering its educational framework, particularly concerning civil servants and teachers. The Ministry of Education confronts challenges including wage inconsistencies, grade/category alignment issues, and teacher entitlements, all contributing to instructional difficulties and the potential for protests. The deficiencies of the current payroll system, encompassing salary disparities, outdated data, and workload discrepancies, amplify discontent, financial insecurity, and perplexity, thus emphasizing the pressing need for system enhancements. Employing a qualitative methodology involving interviews and document analysis, this study delves into the societal, cultural, and political contexts influencing the payroll system. The research scrutinizes the operational mechanisms of the system and the factors influencing its precision and equity, proposing specific measures such as streamlining processes, heightened utilization of information technology, human resources training, and enhanced communication to bolster effectiveness and fairness. These actions aspire to safeguard the well-being and contentment of educators and civil servants, thereby enhancing the calibre of education.